The relationship between changes in functional connectivity gradients and cognitive–emotional disorders in sudden sensorineural hearing loss - Li, Biao; Xu, Xiao-Min; Wu, Yuan-Qing; Miao, Xiu-Qian; Feng, Yuan; Chen, Yu-Chen; Salvi, Richard; Xu, Jin-Jing; Qi, Jian-Wei (Brain communications, 2024)
Abstract Sudden sensorineural hearing loss, a prevalent emergency in otolaryngology, is known to potentially precipitate cognitive and emotional disorders in affected individuals. Extensive research has documented the phenomenon of cortical functional reorganization in patients with sudden sensorineural hearing loss. However, the potential link between this neural functional remodelling and cognitive–emotional disorders remains unclear. To investigate this issue, 30 bilateral sudden sensorineural hearing loss patients and 30 healthy adults were recruited for this study. We collected clinical data and resting-state functional magnetic resonance imaging data from the participants. Gradient mapping analysis was employed to calculate the first three gradients for each subject. Subsequently, gradient changes in sudden sensorineural hearing loss patients were compared with healthy controls at global, regional and network levels. Finally, we explored the relationship between gradient values and clinical variables. The results revealed that at the global level, sudden sensorineural hearing loss did not exhibit significant differences in the primary gradient but showed a state of compression in the second and third gradients. At the regional level, sudden sensorineural hearing loss patients exhibited a significant reduction in the primary gradient values in the temporal pole and ventral prefrontal cortex, which were closely related to neuro-scale scores. Regarding the network level, sudden sensorineural hearing loss did not show significant differences in the primary gradient but instead displayed significant changes in the control network and default mode network in the second and third gradients. This study revealed disruptions in the functional hierarchy of sudden sensorineural hearing loss, and the alterations in functional connectivity gradients were closely associated with cognitive and emotional disturbances in patients. These findings provide new evidence for understanding the functional remodelling that occurs in sudden sensorineural hearing loss. Li et al. reported that patients with bilateral sudden sensorineural hearing loss experience remodelling of the cerebral cortex’s connectivity gradients, which correlates with their cognitive and emotional disorders. The loss of sensory functions leads to abnormalities in higher-order cognitive networks. Graphical Abstract Graphical Abstract